(untitled) (Comprehensive Journal of Science, 2026)
This study aims to analyze the impact of the natural characteristics of the coast on the distribution of fishing activity in the city of Sabratha located on the western coast of Libya. The study focused on several natural factors influencing marine fishing activities, including water depth, seabed nature, and environmental characteristics of seawater, in addition to examining the distribution of fish species across different fishing zones. The study adopted the descriptive analytical approach. Data were collected through field questionnaires distributed to a sample of fishermen in Sabratha city consisting of 75 fishermen, in addition to field observation and reviewing scientific references related to marine geography and fisheries resources. The collected data were analyzed using descriptive statistical methods such as frequencies, percentages, and arithmetic means. The results of the study showed that the natural coastal characteristics play a significant role in determining fishing areas and the distribution of fish species. Some fish species tend to concentrate in shallow coastal areas with sandy seabeds, while others are more common in deeper waters with rocky seabeds. Furthermore, water depth, seabed type, and environmental characteristics of seawater were found to be major factors influencing fishing activity in the study area. The study emphasizes the importance of considering the natural characteristics of the coastal environment when planning marine resource management and regulating fishing activities in order to ensure optimal utilization and sustainability of marine resources along the Libyan coast.